Calculation of Thallium's toxicity coefficient in the evaluation of potential ecological risk index: A case study. (March 2018) - Liu, Yongxia; Wang, Qian; Zhuang, Wen; Yuan, Yanli; Yuan, Yani; Jiao, Keqin; Wang, Mantang; Chen, Qing
Abstract: As a common pollutive metal element, Tl is very biotoxic. The potential ecological risk index (RI) proposed by Håkanson is one of the commonest methods for evaluation of ecological risk of a metal in sedimentary environment of a water body. According to the calculation principle proposed by Håkanson, the toxicity coefficient of Tl was calculated, and determined as 10 in this paper. In addition, the environmental risk of Tl in the surface sediment of the Beijing-Hangzhou Grand Canal (Zaozhuang Section) was evaluated by RI method, enrichment factor method, etc. The South-to-North Water Diversion Project which benefits four billion people is the largest inter-basin water transfer project in China. The Zaozhuang Section is a significant water conveyance line of this project. We found that the Tl concentrations were 0.46–0.70 μg g −1 with the mean value of 0.61 μg g −1 and were higher than the local background value. The highest contents of Tl occurred in the middle of Zaozhuang section and Tai'erzhuang District, but the enrichment degree of it was much higher in the entrance of Nansihu Lake. The grain size and Al oxides/hydroxides were main factors which controlled the distribution of Tl. Analysis of enrichment factors indicated that Tl in sediments possessed obvious source of human activities which were mainly from combustion of fossil fuels such as coal and mining of mineral resources. As a whole, however, the research region has low Tl content, so Tl has a small probability of environmental pollution. Highlights: The toxicity coefficient of Tl was calculated and determined as 10. Tl was obviously enriched in surface sediments of the studied area. Tl possessed obvious source of human activities such as fossil fuels. Tl showed low ecological risk in sediments of the Zaozhuang Section.